Prevalence of Methicillin Resistance Staphylococcus aureus in Community Cases of Pyoderma - Bahram Khan Khoso, Fakhur Uddin, Faiza Zeeshan, Muhammad Anwar, Mir Alam Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the susceptibility pattern of Methicillin-Resistant Staphylococcus aureus (MRSA) isolates of pyoderma cases. Study design: Cross-sectional. Place and duration: Research was conducted in the department of Microbiology in collaboration with the Department of Dermatology, Jinnah Postgraduate Medical Centre, Karachi, during the period of 1.8.2022 to 25.11.2022. Methodology: Total232 pus samples were collected from the clinically suspected patients of pyoderma. Pus swab was cultured on blood and MacConkey’s agar plates. Isolates were identified by routine assay and antimicrobial susceptibility was determined by disc diffusion method. Results: Out of 232 specimens, 196 (84.5%) were culture positive; 170(86.7%) were Gram-positive, 25(12.7%) were Gram-negative and 1(0.6%) was Candida sp. S.aureus was the prevalent offender (119; 51.2%), followed by S.pyogenes (51; 22%) and S.epidermidis (3; 1.3%). S.aureus showed 73(61.3%) MRSA. The highest rate of resistance among all S. aureus was recorded for, penicillin, cefoxitin and ciprofloxacin, 89; 74.7% 73; 61.3% and 72; 60.5% respectively. Conclusion: S.aureus is the prevalent in pyoderma and a significant number was MRSA. Therefore it is mandatory for dermatologist to start the treatment after culture and sensitivity testing is mandatory for failure of treatment and recurrences. Keywords: Methicillin-Resistant Staphylococcus aureus, Pyoderma, S. aureus,Streptococcus pyogenes.